Legal treatment about mental health and family (Papeles, 2024)
This paper provides a systematic review about the importance of the concept of mental health and its treatment within Argentine legal order. It analyzes definitions and their legal context, emphasizing the role of the family. The paper examines the relationship between the Civil and Commercial Code's provisions on capacity restriction and the regulation of mental health law, considering concepts of autonomy and family. Additionally, it discusses fundamental issues and the debate surrounding involuntary hospitalization in relation to the family and identifies implications of the concept of "mental health" in family law institutions, including marriage and parental responsibility.
Keywords: Mental health; family; autonomy